Status and distribution of Eurasian lynx (Lynx lynx) in Slovenia from 2005 to 2009 - Kos, Ivan (Acta biologica slovenica, 2012)
In Slovenia, the status of the re-introduced Eurasian lynx population is monitored using the SCALP (Status and Conservation of Alpine Lynx Populations)methodology. Monitoring is organized by the Slovenia Forest Service in cooperation with other institutions and individuals. We analysed the data for the 2005-2009 monitoring period and compared it with the previousperiods to explore population status and trends for the northern part of the Dinaric population. During this last pentad we recorded six C1 categorydata points, 832 data points of category C2, and 96 points of categoryC3. These numbers are comparable to the previously reported period of 2000-2004. The spatial distribution of signs of lynx presence remained similarcompared to the previous period. Presence and status of the lynx are easier to interpret because of additional telemetry data and a habitat suitability that has been produced since the last report. We assume that this lynx population is critically endangered, because of demographic as well as genetic reasons. To prevent local extinction, an active approach is needed forrevitalization of the population which would address demographic factors aswell as improve the depleted gene pool.
Keywords: Dinaric population; dinarska populacija; distribution; Eurasian lynx; evrazijski ris; Lynx lynx; monitoring; prevalence; razširjenost; Slovenia; Slovenija